Contribution to the Chinese subfamily Rhaphidophorinae Walker, 1869 (Orthoptera: Rhaphidophoridae: Rhaphidophorinae) VIII: Three new species of Sinorhaphidophora from Hainan Province - Bian, Xun (Zootaxa, 2024)
In this paper, I report three new species of Sinorhaphidophora based on newly obtained material from Hainan Province, namely: Sinorhaphidophora longiproceris sp. nov., Sinorhaphidophora gracilenta sp. nov. and Sinorhaphidophora minor sp. nov.. In addition, morphological illustrations of Sinorhaphidophora hainanensis (Bian & Shi, 2016) are provided. All the specimens are deposited in Guangxi Normal University.